On a new environment-friendly gas mixture for Resistive Plate Chambers. (1st May 2022) - Proto, G.; Liberti, B.; Santonico, R.; Aielli, G.; Camarri, P.; Cardarelli, R.; Di Ciaccio, A.; Di Stante, L.; Paoloni, A.; Pastori, E.; Pizzimento, L.; Rocchi, A.
Abstract: This paper studies the performance of RPCs working with a new family of environment-friendly gases, mainly based on Carbon Dioxide and Hydro-Fluoro-Olefins. The tests are carried out on a 2 mm gap RPC and concern the measurement of detection efficiency, avalanche-to-streamer transition probability, prompt and ionic charge delivered. The timing properties of the new gas are also measured.